Examining the Relationship between Organizational Culture and Job Satisfaction in the Department of Public Works - Dr Syed Shameel Ahmed Quadri; Khalaf Abdelfattah Awwad; Sudhair Abbas Bangash; Tariq Rafique; Asifa Zafar, (Dialogue Social Science Review (DSSR), 2025)
Using extensive survey data in Chinese construction firms, this study investigates the link between organizational culture and job satisfaction of employees at the Department of Public Works. The methodology used was primarily quantitative, with the survey piloting a series of established measurement instruments. The data were collected by convenient sampling and absolute assurance of confidentiality was provided which helped in reducing the potential threat from common method variance (CMV). The final sample was made up of 568 employees from various organizational levels. The distribution of respondents by designation, age and work experience was subject to descriptive statistics. Analysis of data was performed via partial least square equation modelling (PLS-SEM) using smart PLS(4), which is a reliable method for assessing associations between constructs. The results indicated a significant association between organizational culture and job satisfaction. The instruments used were the Multifactor Leadership Questionnaire (MLQ) for leadership, the Organizational Culture Assessment Instrument(OCAI), the Competence Assessment of Responsible Employees(CARE) and the Minnesota Satisfaction Questionnaire(MSQ)-for organizational culture to job satisfaction. The results of their analysis show that supportive leadership and positive organizational culture have a significant influence on employee job satisfaction. This was supported by demographic data that highlighted the representation of age groups, "work experience levels", and organizational roles surveys were completed by both management level staff as well non-management. Findings point to the importance of supportive leadership and strengthening competence in respect to organizational culture for job satisfaction, and retention performance. These insights can be used by managers and policymakers in the Department of Public Works to ensure that their subordinates are working as good -happily- slaves. In this paper we build on the URI-DOJ framework and recent empirical literature to address an understudied question: How does organizational culture in public sector agencies relate to job satisfaction within a particular context that involves paid labour employment? Applying PLS-SEM increases the methodological rigour of our study and provides a holistic perspective on the constructs under consideration.